2006
DOI: 10.1364/josaa.23.003114
|View full text |Cite
|
Sign up to set email alerts
|

Scintillation index for two Gaussian laser beams with different wavelengths in weak atmospheric turbulence

Abstract: We study propagation of two lowest order Gaussian laser beams with different wavelengths in weak atmospheric turbulence. Using the Rytov approximation and assuming a slow detector we calculate the longitudinal and radial components of the scintillation index for a typical free space laser communication setup. We find the optimal configuration of the two laser beams with respect to the longitudinal scintillation index. We show that the value of the longitudinal scintillation for the optimal two-beam configurati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…This research derived for the first time the optimal angular separations for multiple transmitter systems for airborne FSOC systems. A majority of previous research on multiple transmitters focused on satellite communications (where the turbulence is only present over a small part of the propagation path) or constant turbulence strength C 2 n paths [4,5,29,59,60,68]. The angular separations for all three airborne geometries (air-to-air, air-to-ground, and ground-to-air) are determined.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This research derived for the first time the optimal angular separations for multiple transmitter systems for airborne FSOC systems. A majority of previous research on multiple transmitters focused on satellite communications (where the turbulence is only present over a small part of the propagation path) or constant turbulence strength C 2 n paths [4,5,29,59,60,68]. The angular separations for all three airborne geometries (air-to-air, air-to-ground, and ground-to-air) are determined.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
“…Much of the research has focussed on multiple Rxs. Some research has been accomplished on multiple-Tx systems, but surprisingly little research can be found on the theoretical angular separation required to take full advantage of these spatial diversity techniques, especially for the airborne application [34,58,59,68]. Rather, most literature on differential statistics for angular separations is concerned with an isoplanatic angle (relatively similar paths) for sensing and wavefront control.…”
Section: Diversity Techniquesmentioning
confidence: 99%
See 3 more Smart Citations